The interrelatedness of organizational ambidexterity, dynamic capabilities and open innovation : a conceptual model towards a competitive advantage - van Lieshout, Johannes W.F.C. (2022)
Purpose – Establishing a competitive advantage in today’s dynamic environment involves optimizing an organization’s exploration and exploitation strategy. This paper aims to explore how an open innovation strategy complements the organization’s ambidextrous strategy in attaining a competitive advantage. Organizational ambidexterity and dynamic capability theories are also explored to investigate the impact of open innovation on the organization’s ambidextrous strategy and competitive advantage – especially inbound and outbound open innovation. Design/methodology/approach – The authors conducted a systematic literature review using Boolean search techniques, which was focused on the research fields of the sub-areas of general management, strategy, innovation, organization studies, information management, entrepreneurship, international business, marketing, and economics, supplemented by the snowball technique. Findings – Organizations that combine their ambidextrous strategy with open innovation attributes achieve a competitive advantage through developing their dynamic capabilities by which organizations change their value proposition. This study also shows that an ambidextrous strategy should no longer be viewed as a structural solution implemented by management, but also as a bottom-up intervention. Additionally, the authors found that the organization’s dynamic capabilities establish a feedback loop, which changes the organization’s ambidextrous strategy to resolve the efficiency–agility paradox. Originality/value – Previous research has focused on strategic orientation; however, hardly any research has investigated how the interrelatedness of open innovation, organizational ambidexterity and dynamic capabilities support a competitive advantage. The authors present a conceptual model that inspires new research avenues